Comparison of compressive fatigue performance of cementitious composites with different types of carbon nanotube. (December 2022) - Li, Linwei; Wang, Xinyue; Du, Hongjian; Han, Baoguo
Highlights: Compressive fatigue property of concrete with different types of CNT is studied. Fatigue life, strength and strain of concrete are greatly improved by adding CNT. Functionalization of CNT cannot further improve fatigue performance of concrete. There is network-like micro-crack formation in concrete with CNT under fatigue. Fatigue striation is observed around the aggregates inside concrete with CNT. Abstract: The compressive fatigue performance of cementitious composites largely depends on the generation and connection of fatigue nano/micro-cracks in the composites. These types of cracks are beyond the scope that traditional fibers can restrain, but can be effectively eliminated and inhibited by incorporating nano-materials, especially those with fiber shape, such as carbon nanotube (CNT). Unfortunately, the effect of CNT and its physical and chemical characteristics on the compressive fatigue performance of cementitious composites remains unclear. Therefore, this paper systematically investigated the effect of CNT with different contents and sizes, functional groups and coating layers on the compressive fatigue performance of cementitious composites, including fatigue life, strength, deformation behavior and cracking characteristics. The morphology of the fatigue fracture surface of cementitious composites shows that CNT can refine pore structure, bridge nano/micro-cracks and result in the generation of the multi-directional and network-like fatigue micro-cracks as well as the appearance of the fatigue striation around aggregates. Consequently, by increasing the integrity among each phase of cementitious composites, CNT significantly maximizes the compressive fatigue life (in logarithmic form), strength and failure strain of cementitious composites by 160 %, 43.4 % and 20.6 %, respectively, showing great potential for extending the service life of concrete structures.